Citizen Perception of e-government in the Ministry of Transport and Public Works of Ecuador: A Quantitative Correlational Analysis - García Briones, Martha Yadira (2026)
The public service in Latin America is characterized by growing demands for efficiency, transparency, and accessibility in a national context driven by dynamics of socioeconomic inequality and limited trust in institutions. E-government is presented as a strategic tool to address these dynamics through the digitalization of processes, streamlined access to public information, and the full exercise of citizen participation. The goal of this study was to analyze citizen perceptions of the impact of e-government on the Ministry of Transportation and Public Works of Ecuador, identifying achievements, weaknesses, and structural challenges. The research followed a quantitative approach, with a non-experimental, descriptive, and correlational design, presenting structured surveys administered to 200 users in five Ecuadorian provinces. The instrument was structured in four dimensions: access to digital platforms, service quality, institutional transparency, and citizen participation, yielding a Cronbach's alpha of 0.87. The results showed favorable access to digital platforms; however, technical support challenges persist for proper functioning. Service quality, meanwhile, is perceived as moderate due to persistent technical issues, while institutional transparency shows progress in information accessibility, but with concerns regarding data protection. On the other hand, the correlational analysis finds a more robust relationship between service quality and citizen participation. It is stated that Ecuadorian e-government requires a comprehensive approach focused on technological infrastructure, support, territorial equity, and citizen digital governance.